Generalized Interval-Valued Neutrosophic Set and Its Application - Anjan Mukherjee; Rakhal Das (Transactions on Fuzzy Sets and Systems)
In this work, we introduce the idea of generalized interval-valued neutrosophic sets. After providing the fundamental definitions of operations related to these sets, we establish several key properties and explore the relationships between generalized interval-valued neutrosophic sets and other related concepts. Finally, we extend the notion of generalized neutrosophic topological spaces to incorporate generalized interval-valued neutrosophic topological spaces. We define the concept of generalized interval-valued neutrosophic g-continuous function between two generalized interval-valued neutrosophic topological spaces. Lastly, an application has been shown in decision making problem.